Implementation of the Policy on the Use of Corona Virus Disease 2019 Vaccine Cards as a Requirement for Aviation Administration at Sultan Bantilan Airport, Galang District, Tolitoli Regency - Masrin Gafar (Formosa Journal of Sustainable Research, 2022)
The purpose of this study was to determine the implementation of the policy of using the Corona Virus Disease 2019 (Covid-19) vaccine card as a condition for flight administration at Sultan Bantilan Airport, Galang District, Tolitoli Regency in breaking the chain of transmission of Covid-19. This type of research is descriptive with a qualitative approach. Informants selected 6 people with purposive sampling technique. Collecting data through observation, interviews and documentation. Furthermore, through the stages of data reduction, data presentation, and drawing conclusions. The results of the study were analyzed using the policy implementation success model of Merilee S. Grindle. The results of the research show that Sultan Bantilan Tolitoli Airport clearly understands the rules for using the Covid-19 vaccine card as a requirement for flight administration when traveling by air during a pandemic as stipulated in Circular Letter Number 96 of 2021 concerning Guidelines for Implementing Domestic Travel during the Period Covid-19 pandemic. However, it is still lacking in outreach to prospective passengers. Likewise, the determination of administrative fees for the swab rapid test antigen is considered burdensome and the rejection of vaccination by prospective passengers